Optimization of Hybrid Laminates with Extension-Shear Coupling - Da Cui; Daokui Li (International Journal of Aerospace Engineering)
The introduction of hybrid composites into the structure with coupling effect can greatly reduce the cost of materials. The expressions of stiffness coefficient, thermal stress, and thermal moment for hybrid laminates are derived based on the geometrical factors of laminates, and the necessary and sufficient conditions for the hybrid extension-shear-coupled laminates with immunity to hygrothermal shear distortion (HTSD) are further derived. The extension-shear-coupled effect of hybrid laminates is optimized with improved differential evolution algorithm. Results are presented for the hybrid laminates that consist of carbon fiber and glass fiber composite materials. The hygrothermal effect and extension-shear-coupled effect are simulated and verified, meanwhile the robustness of hybrid laminates is analyzed by Monte Carlo method.